2008
DOI: 10.1203/pdr.0b013e31817d9bb0
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen Versus Continuous Indomethacin in Premature Neonates With Patent Ductus Arteriosus: Is the Difference in the Mode of Administration?

Abstract: Ibuprofen has been proposed as a preferential alternative to indomethacin in treating patent ductus arteriosus (PDA), because it is purported to have less renal, mesenteric, and cerebral vasoconstrictive effects. However, short and long-term safety concerns regarding ibuprofen remain. Continuous slow infusion of indomethacin also eliminates peripheral vasoconstriction and may thus offer similar benefits to ibuprofen without safety concerns. In this study, our objective was to show that treating a PDA with cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 33 publications
2
27
0
5
Order By: Relevance
“…62 Another potential group at risk is infants younger than 6 months because of the possibility of differences in ibuprofen pharmacokinetics and developmental differences in renal function. 65 Data are inadequate to support a specific recommendation for the use of ibuprofen for fever or pain in infants younger than 6 months (there are dosing data for neonatal closure of patent ductus arteriosus 66,67 ), although the package insert states to "ask a doctor" for guidance on its use in this population. Another potential risk associated with the use of ibuprofen is the possible association between ibuprofen and varicella-related invasive group A streptococcal infection.…”
Section: Ibuprofenmentioning
confidence: 99%
“…62 Another potential group at risk is infants younger than 6 months because of the possibility of differences in ibuprofen pharmacokinetics and developmental differences in renal function. 65 Data are inadequate to support a specific recommendation for the use of ibuprofen for fever or pain in infants younger than 6 months (there are dosing data for neonatal closure of patent ductus arteriosus 66,67 ), although the package insert states to "ask a doctor" for guidance on its use in this population. Another potential risk associated with the use of ibuprofen is the possible association between ibuprofen and varicella-related invasive group A streptococcal infection.…”
Section: Ibuprofenmentioning
confidence: 99%
“…17 Indomethacin reduces the blood flow velocity in kidneys, intestine, and brain, ibuprofen has not this effect. 1,14 In infants who received 2 or more courses, the decrease in urine output and the increase in serum creatinine concentration were not different between ibuprofen and indomethacin.…”
Section: ■ Discussionmentioning
confidence: 96%
“…Ibuprofen and indomethacin in neonates Pacifici GM Similar results were described by Yang et al, 18 comparing 26 low weight birth babies who received intravenous indomethacin with 22 preterm infants who received oral ibuprofen. 14 The overall rate of ductal closure was 88.5% indomethacin and 81.8% with ibuprofen. Lee et al 19 compared the effects and complications of ductus arteriosus closure intravenous indomethacin (n = 85) vs oral ibuprofen (n = 52) in neonates weighing < 1500 grams.…”
Section: Intravenous Indomethacin Vs Oral Ibuprofenmentioning
confidence: 94%
See 1 more Smart Citation
“…We speculate that these improved results obtained through oral administration compared with the traditional intravenous route stem from the longer maintenance of therapeutic plasma levels over time, extending the drug's effect on the receptors within the ductus arteriosus. This hypothesis is supported by another study that showed better results with continuous indomethacin infusion when compared with ibuprofen or the regular three dose regimen of indomethacin to close the PDA 25. A search of the literature revealed limited data regarding the plasma levels of ibuprofen following oral administration.…”
Section: Introductionmentioning
confidence: 88%